Does alcohol consumption affect life expectancy in OECD countries? - Gavurová, Beáta; Ivanková, Viera; Rigelský, Martin (Adiktologie, 2020)
BACKGROUND: The consumption of different types of alcoholic beverages leads to different health risks. Therefore, different effects on the health of the population can be expected. AIM: The main objective of the study was to assess the relations between the consumption of selected types of alcoholic beverages and the life expectancy of the population in OECD countries. METHODS: Non-parametric analysis of relationships (Spearman ρ) and simple linear quartile regression analysis were used to meet the objective. SAMPLE:The research covered 36 countries of the Organisation for Economic Co-operation and Development (OECD). In the analytical procedures, four main types of alcoholic beverage were used: (i) beer, (ii) wine, (iii), spirits, (iv) other. The consumption of individual types of alcohol in each country was expressed in litres of pure alcohol per person (aged 15+ years) per year. The analysis also included a health variable determining life expectancy at birth. All data was collected for the period from 2010 to 2017. RESULTS: In terms of the consumption of common types of alcoholic beverages (beer, wine, spirits), a significant effect on life expectancy was found. Beer and spirits showed a negative effect, i.e. with increased consumption of beer and spirits, a decrease in life expectancy can be expected. On the other hand, wine consumption had a positive effect on life expectancy. A significant positive relationship was identified between the consumption of beer and of spirits, i.e. with an increase in the consumption of beer, an increase in the consumption of spirits can be expected. CONCLUSIONS:Prevention and education should focus in particular on the countries of Central and Eastern Europe, as higher consumption of beer and spirits was found in some of these countries. Lower alcohol consumption in these countries could have a positive effect on life expectancy.